If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-(X+6)=2X-11
We move all terms to the left:
4-(X+6)-(2X-11)=0
We get rid of parentheses
-X-2X-6+11+4=0
We add all the numbers together, and all the variables
-3X+9=0
We move all terms containing X to the left, all other terms to the right
-3X=-9
X=-9/-3
X=+3
| 171=335-g | | 116-5d=56 | | d/8-3=10 | | 3x-4/5=8 | | y-49=276 | | d-2=296 | | h^2-2h-80=0 | | w/8+47=50 | | 1/2(2h-4)h=80 | | 28+5h=83 | | h+76=96 | | 2=c/7-2 | | 8h+7=47 | | 8y-8=72 | | 5/14n-8=2 | | 8y-8=48 | | 1/5s=16 | | 25z+62=212 | | 3a-3/6=4a-1/15+2 | | 14+7x=28 | | t=749-653 | | n-13/4=41/2 | | b/5+169=185 | | 0.6x-5=0.1x+5 | | n^2+11n+12=0 | | 42=5h-13 | | -7v=17 | | 32/r=4 | | 3a-3/6=4a=1/15+2 | | h/8=5 | | t+66=4t | | 5=g/9-5 |